Hepatitis C Virus in Pregnancy: Case Reports and Literature Review. Issue 6 (1995) - Joffe, Gary M.
Abstract : Background: Hepatitis C virus (HCV) is now recognized as the cause of 90% of non-A, non-B (NANB) hepatitis. This virus is responsible for a large percentage of chronic persistent and chronic active hepatitis in the United States. Parenteral and sexual transmission are well described, so a significant population of pregnant patients is at risk. Vertical transmission of the virus to the fetus is dependent upon the level of maternal viremia. Case: The cases described in the following report demonstrate that fulminant disease may present in pregnancy. They also demonstrate the cofactors promoting the severity of illness, methods of diagnosis, potential treatment, and outcome of the infection. Conclusion: HCV may be encountered in pregnancy. Although most acute-phase illness will be self limiting, some patients will manifest liver failure during gestation. Because vertical transmission to the fetus is possible, the pediatrician should be informed of the maternal disease. Chronic hepatitis is almost the rule rather than the exception, so patients require close postpartum follow-up. Interferon, which may alter the course of the chronic disease, has been used on rare occasions in pregnancy.